RJFA 2020
DOI: 10.7176/rjfa/11-14-07
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Disclosure and Financial Performance of Firms in Kenya: A Stakeholder Approach

Abstract: Using panel data analysis this study examined the influence of environmental disclosure in annual reports on financial performance of companies listed on the Nairobi Securities Exchange in Kenya. Environmental disclosure information was collected using quantitative content analysis for the period 2007-2015 while financial performance data was collected for the period 2008-2016, a one-year lag behind the environmental disclosure data. Control variables were firm size, industry type and leverage. Environmental d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 43 publications
2
3
1
Order By: Relevance
“…This suggested that corporate sustainability had a positive effect on shareholders' wealth in the national financial sector in Nigeria. This is consistent with previous studies by [30,34,29,32,39,25,[51][52][53]. For instance, Pedron et al looked into how environmental disclosure affected Sustainable Stock Returns (SSR) and market share prices of companies listed in Brazil, and they discovered that environmental disclosure had a favourable impact on both stock returns and market values of the sampled companies listed in Brazil [30].…”
Section: Discussion Of Findingssupporting
confidence: 86%
See 1 more Smart Citation
“…This suggested that corporate sustainability had a positive effect on shareholders' wealth in the national financial sector in Nigeria. This is consistent with previous studies by [30,34,29,32,39,25,[51][52][53]. For instance, Pedron et al looked into how environmental disclosure affected Sustainable Stock Returns (SSR) and market share prices of companies listed in Brazil, and they discovered that environmental disclosure had a favourable impact on both stock returns and market values of the sampled companies listed in Brazil [30].…”
Section: Discussion Of Findingssupporting
confidence: 86%
“…The research of Pedron et al and Wara et al complement one another. The study's findings showed that environmental disclosure indices in the examined region had a favourable and significant impact on company performance as evaluated by Tobin's Q [30,34].…”
Section: Empirical Reviewmentioning
confidence: 87%
“…The result of the regression analysis revealed that environmental disclosure measured using economic, social and governance (ESG) revealed a positive significant effect on return on assets and corporate sustainability reporting of the selected and sampled companies in Nigeria. Emeka et al (2020) had a result that is in concordance with the result obtained by (Wara et al, 2020). The study concluded that environmental disclosure had a positive influence on the corporate profitability of the companies sampled.…”
Section: Theoretical Frameworksupporting
confidence: 71%
“…The result of the study revealed that corporate performance measured using Tobin's Q and return on assets (ROA) was positively and significantly affected by environmental disclosure indices. Wara et al (2020)'s result is not different from the result derived from (Nguyen & Tran, 2019). The regression analysis revealed that environmental accounting disclosure had a positive significant association with financial performance for the period under consideration in the study.…”
Section: Theoretical Frameworkmentioning
confidence: 57%
See 1 more Smart Citation